2014
DOI: 10.1111/acem.12554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Glasgow‐Blatchford and AIMS65 Scoring Systems for Risk Stratification in Upper Gastrointestinal Bleeding in the Emergency Department

Abstract: ObjectivesThe aim of this study was to compare the performance of the Glasgow‐Blatchford and the AIMS65 scoring systems as early risk assessment tools for accurately identifying patients with upper gastrointestinal (GI) bleeding who are at a low risk of requiring clinical interventions, including emergency endoscopy. The secondary objective was to compare their performance regarding relevant clinical outcomes.MethodsData were collected prospectively over a 2‐year period in the emergency department of a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 27 publications
6
58
1
2
Order By: Relevance
“…Previous studies have shown that for predicting the need for a blood transfusion, the GBS was better than other scores (3,17,20). A comparison of both scores for prognosticating the need for transfusion shows that the GBS has a higher predictive power than the AIMS-65 score (AUC=0.660 vs. AUC=0.611; p=0.001).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous studies have shown that for predicting the need for a blood transfusion, the GBS was better than other scores (3,17,20). A comparison of both scores for prognosticating the need for transfusion shows that the GBS has a higher predictive power than the AIMS-65 score (AUC=0.660 vs. AUC=0.611; p=0.001).…”
Section: Discussionmentioning
confidence: 83%
“…Esophageal varices (37%) were the most common finding, followed by gastritis (16%), among those who had endoscopy for UGI bleeding. Similarly, Alema et al (32), in their study of 224 patients, recorded that 40.6% suffered from esophageal varices, and Yaka et al (17), in their study of 254 patients, showed that 16.5% of their patients had gastritis. However, Dicu et al (3) also revealed that 41.4% of patients had gastric/duodenal ulcers and that only 27.9% had esophageal varices.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This score uses five factors (albumin, INR, altered mental status, systolic blood pressure and age) that are deeply related to inpatient mortality: 0 risk factors are associated with a mortality rate of 0.3%, while 5 risk factors predict a mortality rate of 25% (27). Comparative studies between AIMS65 score and GBS have reached divergent conclusions.…”
Section: Risk Stratificationmentioning
confidence: 99%